Mating system of Centaurea aspera (asteraceae) polyploid relatives - Short communication. (4th May 2021) - Ferriol, María; Garmendia, Alfonso; Benavent, David; Ferrer-Gallego, P. Pablo; Merle, Hugo
Abstract: Centaurea aspera polyploid complex represents a comprehensive model. The aim of this short communication was to study the mating system of the three main species. The results showed that allotetraploid C. seridis was self-compatible (SC), while autotetraploid C. gentilii was self-incompatible (SI) as the diploid parental C. aspera (SI).